Identification of Diesel Resistant Bacteria that Isolated from Ship Dismantling Area in Madura Coastal - Harmin Sulistyaning Titah; Herman Pratikno; Atiek Moesriati; Rizky Islami Putera; Muhammad Fauzul Imron (International Conference on Coastal and Delta Areas, 2017)
Ship dismantling activity is one industry that caused diesel contamination in environment. One of technology that can be used to remediate diesel contaminated area is bioremediation. Bioremediation can be conducted using bioaugmentation technique. The objective of this study was to identifity of diesel resistant bacteria using biochemicals test methods. The seawater and coastal soil samples were collected from area study using a sterilized bottles. All samples were shaker at 150 rpm for 1 h, after that samples were taken and serially diluted from 10-1 to 10-7. The diluted sample was inoculated on nutrient agar plates by pour plate method. The plate was incubated for about 24-48 hours and the growth of microorganisms was noted. Bacteria with difference of colony morphologies were selected. The cell morphology was determined microscopically after Gram-stain preparation. The isolates were identified using Microbact GNB 12A and 12B (Oxoid, UK) identification kit. This is a miniaturized computer aided identification system for the identification of organisms belonging to the genus Acinetobacter and Vibrio. Keywords: bacteria, bioremediation, coastal, seawater, ship dismantling